Combined effects of cancer and prothrombotic genotypes on the risk of venous thromboembolism - Skille, Hanne (UiT The Arctic University of Norway, 2021)
Venous thromboembolism (VTE), a collective term for deep vein thrombosis and pulmonary embolism, is a severe and multifactorial disease. Heritability has been found to explain up to 60% of VTE events, however, the role of genetics on VTE in cancer is scarcely studied. VTE occurs frequently in cancer patients and is a common cause of morbidity and mortality in this patient group. The aim of the present thesis was to investigate the impact of individual prothrombotic genotypes and the combination of genotypes in a genetic risk score (GRS) on the risk of VTE in cancer patients. Further, VTE may be the first sign of an underlying malignancy, and therefore we also aimed to investigate the effect of prothrombotic genotypes on VTE risk in subjects with an occult (i.e. undetected) cancer. All four papers in the present thesis utilize data from the fourth survey of the Tromsø Study (Tromsø 4), conducted in 1994-1995. The study populations in Paper I and III are also recruited from the second survey of the Nord-Trøndelag Health Study (HUNT 2), conducted in 1995-1997. Paper IV is based on the Scandinavian Thrombosis and Cancer (STAC) Cohort, which consists of merged data from the Tromsø 4 Study, the HUNT 2 Study and the Danish Diet, Cancer and Health (DCH) Study. Participants were followed from date of enrollment (1993-1997) in the different surveys to the date of an incident VTE event, the date of death or migration, or until end of follow-up (2007-2012). All potential cases of incident VTE events and cancer diagnoses during this time-period were recorded. We reported the effect of several single nucleotide polymorphisms (SNPs) on VTE risk in subjects with and without cancer. A SNP of the GP6 gene (rs1613662), affecting platelet adhesion and activation, displayed a decreased risk of VTE in cancer-free subjects, while an increased risk was observed in cancer patients homozygous for GP6 SNP. The genotype was also found to be associated with prothrombotic and metastatic cancers. These findings support a role of platelet ...